MOTIVATION TO CONSUME ZAMZAM WATER: SCIENTIFICALLY AND FROM A MUSLIM PERSPECTIVE IN STUDENT ENVIRONMENT - Hermawan, Muhamad Fauzan; Putri, Davina Aulia; Priyana, Ekky Purwa; Darmawan, M. Rafael Ichwan; Faqihuddin, Achmad (Program Pascasarjana UIN Sumatera Utara, 2024)
Many Muslims are competing to be able to drink Zamzam water because of various motivations with good hopes and prayers in it, thus this research has the aim of being a form of scientific evidence and proving the perspective of people who have consumed the water. The Zamzam. This research model uses qualitative models accompanied by literature studies, with techniques of directly interviewing female students who live around the city of Bandung. The research results obtained mostly believe that the motivation to consume Zamzam water is because of its history and blessings and is strengthened by support from a scientific perspective as well.